2018
DOI: 10.1155/2018/1836836
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Antimicrobial Use Practices among Tennessee Dairy Cattle Producers

Abstract: Nonjudicious antimicrobial use (AMU) and inadequate antimicrobial stewardship are known modifiable factors driving the occurrence of antimicrobial resistance (AMR). A mixed methods approach using a combination of focus groups and survey questionnaires was used to explore the AMU practices of Tennessee (TN) dairy cattle producers. Specifically, the objectives of the study were to determine the following: (1) the most common drivers for using antimicrobials, (2) perceived alternatives to antimicrobials, (3) know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 38 publications
(49 reference statements)
3
53
0
Order By: Relevance
“…Based on this study, Gram-negatives are more resistant than Gram-positives but whether this difference is due to intrinsic resistance of Gram-negatives to some of these antimicrobials or due to the development of resistance under the presence of antimicrobials prescriptions need further investigation. The fitness to thrive under antimicrobials may be acquired and promoted due to the frequent imprudent use of antimicrobials in dairy farms in the study area since an unregulated imprudent antimicrobial use pattern was reported among dairy farmers in Tennessee [ 62 ]. However, we do not have antimicrobials use patterns of farms included in this study to support this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this study, Gram-negatives are more resistant than Gram-positives but whether this difference is due to intrinsic resistance of Gram-negatives to some of these antimicrobials or due to the development of resistance under the presence of antimicrobials prescriptions need further investigation. The fitness to thrive under antimicrobials may be acquired and promoted due to the frequent imprudent use of antimicrobials in dairy farms in the study area since an unregulated imprudent antimicrobial use pattern was reported among dairy farmers in Tennessee [ 62 ]. However, we do not have antimicrobials use patterns of farms included in this study to support this finding.…”
Section: Discussionmentioning
confidence: 99%
“…The first point to be presented here, “Treatment practices” ( Figure 1 , intrinsic, common factor), appeared to be an important point for both veterinarians and farmers, with a range of attitudes on how to approach treatment. Several studies suggest that veterinarians and farmers both agree that sick animals need treatment [( 29 ), 44–5, ( 30 ), p. 86, ( 31 ), p. 4, ( 32 ), p. 7], yet motives seem to differ between the two groups. According to Speksnijder et al [( 29 ), p. 44], veterinarians regard diseased animals from a professional and ethical point of view, with treatment primarily related to their perceived obligation as a veterinarian to ensure animal health and welfare.…”
Section: Intrinsic Factors Affecting the Intention To Move Towards Ramentioning
confidence: 99%
“…Other perceptions about “Treatment practices” have also been identified in the literature ( Figure 1 , intrinsic, common factor). Several studies found that both veterinarians and farmers believe that vaccination plays a key role in reducing AMU [( 32 ), p. 11, ( 31 ), p. 7, ( 35 ), p. 5–7, ( 36 ), p. 3232–7]. However, vaccination was perceived as ineffective among farmers in Washington State [( 36 ), p. 3234].…”
Section: Intrinsic Factors Affecting the Intention To Move Towards Ramentioning
confidence: 99%
See 1 more Smart Citation
“…The VFD only authorizes the use of medically important antimicrobials in feed and water for therapeutic purposes, under the supervision of a licensed veterinarian. In Tennessee (TN), we found that the VFD, and other factors such as producer’ experience and peer support, and antimicrobial drug attributes drive AMU [18, 19]. A previous review that evaluated evidence on the unintended consequences of AMU restrictions in food animals recommended that more research should be conducted to evaluate, document, and report the unintended consequences of interventions targeting AMR reduction [9].…”
Section: Introductionmentioning
confidence: 99%